Integrasi Nilai Moderasi Beragama dalam Proses Belajar Pendidikan Agama Islam di Sekolah - Idris, Irfan; Usman, Syahruddin (Jurusan Tarbiyah STAI Al-Gazali Bone, 2025)
Religious moderation has become an important issue in Islamic religious education amid the reality of social diversity in Indonesia. Islamic Religious Education in schools plays a strategic role in shaping students’ balanced, tolerant, and inclusive religious attitudes. This article aims to examine the integration of religious moderation values in the learning process of Islamic Religious Education in schools. This study employs a literature review approach by analyzing relevant academic sources, including books, journal articles, and educational policy documents. The findings indicate that the integration of religious moderation values can be systematically implemented through the development of contextual learning materials, the application of dialogical and reflective learning methods, and the strengthening of humanistic educational interactions. Such integration contributes to the formation of students’ moderate religious character and their ability to live harmoniously in a diverse society.